Announcements - Bankauskaitė, Gabija (Respectus Philologicus, 2018)
14–18 May, 2018, 22–26 October, 2018, 28 January – 1 February, 2019 in Florence (Italy) will be held the Intensive Course Training for Trainers. Life Beyond Tourism® invites to attend the course and become a Certified Trainer of the Life Beyond Tourism Movement in your university/institution. This course is a five days high-level preparation for professionals and teachers in the fields of education, tourism and heritage, who wish to upgrade their specialisation with the fundamentals of the philosophy and movement Life Beyond Tourism®. Participants will acquire solid theoretical and practical basis along the educational methodology developed by Life Beyond Tourism®. The future trainers will therefore be able to ensure the continuity of the didactic approach used by trainers while imparting Life Beyond Tourism® in their home institutions throughout the world. Finally, participants will be required to draft a personal training action plan reflecting their vision on the Life Beyond Tourism® training activities. Special conditions are available for the Experts of the Foundation and the staff of the universities which signed the Memorandum of Understanding Life Beyond Tourism or the 2014 Declaration of Auspices Life Beyond Tourism for UNESCO. More information here http://www.istitutointernazionalelbt.org/en/corsi-lbt/formazioneper-formatori/; Simone Giometti secretarygeneral@fondazione-delbianco.org. During the Intensive Course Training for Trainers, a student workshop The international students workshop “Linguocultural Space of the City with Special Reference to World Famous People and Florentine Handicrafts” is planned for 22–26 October, 2018 in Florence (Italy). The project aims at studying Florentine cultural heritage and reflection of its influence in both Italian and world cultures presented in the works of world famous handicrafts of Florentine cultural who once lived in or visited Florence and got inspired by the ci ty, its museums, monuments, architecture and people. The purpose of the project is to show the links of the outstanding people with Florence and Florentine artistic atmosphere as seen by international students. The proposed project of a new multimedia Internet lexipedia is based on the analysis of various sources (encyclopedias, books, journals, memoirs, personal letters, etc.) about famous Italians of all epochs along with personal experience gained by international students during their stay in Florence due to visiting Florentine museums, art galleries, libraries, and research centres. Each group of students is supposed to submit their own vision of a dictionary and its articles devoted to distinguished people (handicraftsmen, etc.) whose creative career was connected with Florence. Specification on the participants: undergraduate and postgraduate students, professors of the universities, practical workers specializing in the field of literature, art and culture, author dictionaries study and dictionary making. People interested in literature, art and music are welcome to join the project. More information here http://www.lifebeyondtourism.org/events/linguocultural-space-iilbt/; Екатерина Григорьева greekat@yandex.ru. 25–27 October, 2018 in Jagiellonian University, Kraków (Poland) will take place The Seventeenth International Conference on the Literature of Region and Nation Aftermath: The Fall and the Rise after the Event – Incorporating. The goal of the conference, jointly organised by the Institute of English Studies (Jagiellonian University in Kraków), the Institute of Art History (University of Warsaw) and the Region and Nation Literature Association, is to explore the notion and representation of aftermath, understood as a consequence/result/after-effect of a seminal event (to an individual, a community, society, regions and nations) whose nature is not necessarily unfortunate and disastrous but certainly transformative and life-changing. We are particularly looking forward to receiving proposals addressing the issue of aftermath’s revolutionary and subversive potential in literary fiction and non-fiction, art and various types of visual narratives. Proposals for 20-minute presentations should consist of a brief biographical note (including academic title and institutional affiliation) and a 150-word abstract. They should be sent to aftermath. conference@gmail.com by 31 May 2018. More information here www.aftermathconference.wordpress.com. Dear colleagues! The information about conferences, seminars and other scientific events of your institution please send to respectus.philologicus@knf.vu.lt